2002
DOI: 10.1038/sj.onc.1205534
|View full text |Cite
|
Sign up to set email alerts
|

Expression of thyroid hormone receptor/erbA genes is altered in human breast cancer

Abstract: The relation between thyroid status and diseases and cancer is unclear. No detailed analysis of thyroid hormone receptor (TR) expression in human breast cancer has been reported. We have analysed the expression and mutational status of the TRa1, encoded by the c-erbA proto-oncogene, TRb1 and TRb2 isoforms in 70 sporadic breast cancers. Alterations in the RNA level of TRb1, TRa1, or both were found in a number of patients. No expression of TRb2 RNA was detected. Western blotting analysis con®rmed the di erences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 53 publications
3
68
0
Order By: Relevance
“…Moreover, hyperthyroidism accounts for 2% of all patients presenting adult gynecomastia (12) and it has also been suggested that free triiodothyronine (T 3 ) plays an important role in the physiology of fibrocystic breast disease (13). Consistent with the proposal that thyroid hormones act on the breast, TR have been described in breast cancer (14).…”
Section: Introductionsupporting
confidence: 51%
“…Moreover, hyperthyroidism accounts for 2% of all patients presenting adult gynecomastia (12) and it has also been suggested that free triiodothyronine (T 3 ) plays an important role in the physiology of fibrocystic breast disease (13). Consistent with the proposal that thyroid hormones act on the breast, TR have been described in breast cancer (14).…”
Section: Introductionsupporting
confidence: 51%
“…Few studies have reported clear results demonstrating associations, although in these studies, TRs and other histopathological findings were not further differentiated; for example, a negative correlation between the TR receptor level and the axillary involvement of lymph nodes (29). By contrast, Silva et al did not find clear correlations between single TRβ1 expression and other histopathological factors (30). The inconsistency between the results of different TRs may be attributable to different distributions of the TRs in the examined tissue (certain (31,32).…”
Section: Discussionmentioning
confidence: 82%
“…This expression is limited to the adult mammary gland (120) and related to mammary gland proliferation and differentiation (110,(121)(122)(123)(124)(125), but is commonly absent in healthy breast tissue samples. The detection frequencies seem to vary (126)(127)(128), sensitivity of qPCR for detection of hMAM mRNA shows a broad range even in metastatic breast cancer (128)(129)(130), imposing doubt on the utility of this marker (118), but a combination of hMAM with survivin and hTERT increases the sensitivity of CTC detection (131), pointing towards the use of multimarker PCR (132). Furthermore, no correlation could be found between the expression of hMAM and nodal state, tumour size and grading (109,121,132).…”
Section: Rt-pcr Marker Genes For Ctc Detectionmentioning
confidence: 99%